Review Progres Agropolitan pada Strategi dan Trend Ekspor Jagung di Gorontalo - Hendra Haipi; Dewa Oka Suparwata; Merita Ayu Indrianti; Aditya Djaini (Student Scientific Creativity Journal, 2026)
. The Agropolitan Program based on corn commodities in Gorontalo Province aims to enhance agricultural productivity, improve farmers’ welfare, and strengthen the competitiveness of corn. This study examines the progress of program implementation and its impact on production, quality, export volume, and competitiveness. A quantitative approach was employed, utilizing SWOT analysis and the Revealed Comparative Advantage (RCA) method. Data were obtained from the Central Bureau of Statistics, relevant institutions, as well as limited observations and interviews.The results indicate that the Agropolitan Program has contributed positively to the expansion of harvested areas and increased corn production, particularly during the 2020–2024 period. This increase is not only evident in terms of quantity but has also begun to show improvements in the quality of yields, although these improvements are not yet evenly distributed across regions. However, export performance remains fluctuating, with unstable RCA values, indicating that the competitiveness of corn in the international market still faces various challenges.This condition is influenced by limitations in logistics infrastructure, weak farmer institutions, dependence on middlemen, and the suboptimal integration of the value chain from upstream to downstream. In addition, access to technology, financing, and market information remains a significant constraint that needs to be addressed. It is concluded that the success of the program requires strengthening institutional capacity, improving distribution efficiency, and implementing sustainable and integrated export policies to support the stability and long-term competitiveness of corn.